PENGARUH RELEVANSI (OMNIBUS LAW) TERHADAP KINERJA KARYAWAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA - Deyva Putri Juhanto; Dian Sudiantini, Muhamad Fadil Akbar, Mursyidan Ahmad Naji, Ida Bagus Aditya Sueken (CV. Adiba Aisha Amira, 2024)
In implementing public policy, it goes through several stages before it is actually realized, one of which is the formulation stage, for example the Omnibus Law on the Job Creation Bill. The presence of omnibus law has actually become a bad scourge for workers and other workers. The method used in writing this scientific paper is the literature study research method (Library Research) and is included in qualitative research. The findings of this research reveal a bright spot, namely that omnibus law specifically only benefits investors or corporations and forgets about fulfilling performance rights for workers, one of which is reducing the minimum wage and terminating work without demands.